MEMBANGUN KINERJA PEMERINTAH DALAM MENINGKATKAN EFEKTIVITAS PEMBANGUNAN DESA DI KABUPATEN MAJALENGKA - Ade Solihin; Diding Bajuri; Kania Agustina (DIALOGIKA, 2022)
Independent village development can result from good performance of government organizations, so that it will produce effective and quality village development. This study analyzes the influence of government organizational performance factors on the effectiveness of village development. The method used is descriptive quantitative with primary and secondary data collection. The population of this research is elements of village government officials who are in 5 villages with the sampling technique carried out by total sampling of 64 village officials. The results of the descriptive research show that village development is largely determined by the professional attitude of the apparatus in order to realize a performance-based budget to achieve effective village development. The results of the verification research show that organizational performance has a significant influence on the effectiveness of village development.